Argumentación Jurídica para sancionar las contravenciones de tránsito y su incidencia constitucional en el debido proceso - Chiriboga Zamora, Janeth Jacinta (2015)
After having met the basic requirements for submitting a draft and you have made the changes suggested by the experts, the thesis topic has been left with the following title: "LEGAL ARGUMENT TO PUNISH THE TRAFFIC VIOLATIONS AND ITS IMPACT ON CONSTITUTIONAL DUE PROCESS. " It has been verified that that issue has no documentation like it or relate directly, since this is an authentic and unique perspective, which arises from the initiative of the research, to be applied as a thesis at the School of Law. It will seek to document the investigation, legal and transit elements linked to the management by the competent institution at the level of the city of Quevedo, an area in which research has identified. It will mean a contribution to other similar studies that may arise regarding traffic conflicts and improving public cultures based on the Good Living and respects the rules and rights of individuals.